Culture conditions and treatments affect Caco-2 characteristics and particle uptake. - Moyes, S; Morris, J; Carr, K (2010)
Small intestinal microparticle uptake via a paracellular route is relevant to oral drug delivery and environmental pollution. In vitro investigation uses latex microparticle passage across a confluent Caco-2 cell epithelium. This paper examines the influence of culture conditions on transepithelial resistance (TER); cell dimensions from confocal microscopy; and number of particles below the epithelium. Variables investigated include level of initial TER; multiple TER measurements; involvement of medium; cell source; and pretreatment with ethanol or a range of temperatures. Data were collected after exposure to 2 microm latex particles for 5-120 min: sham groups were exposed to pretreatment but not particles. The results highlight the importance of very precise control of the experimental environment; confirm the pattern of sequential-TER increase/decrease in groups exposed only to particles and show accompanying increases in cell dimensions. Greater particle uptake was associated with ethanol-induced decreased TER, decreased cell height and increased intercellular spaces, similar to previous findings for external irradiation. Low temperatures raised TER but, despite this, cooling did not alter particle uptake. In conclusion, culture microenvironment and sham treatment are crucial considerations in studies of epithelial microparticle uptake in vitro.